The Influence of the German Capitalization Rules on Reading - Pauly, Dennis Nikolas; Nottbusch, Guido (Frontiers in Communication, 2020)
German orthography systematically marks all nouns (even other nominalized word classes) by capitalizing their first letter.It is often claimed that readers benefit from the uppercase-letter syntactic and semantic information,which makes the processing of sentences easier (e.g Bock et al. 1985, 1989). In order to test this hypothesis, we asked 54 German readers to read single sentences systematically manipulated by a target word (N).In the experimental condition (EXP), we used semantic priming (in the following example: sick → cold) in order to build up a strong expectation of a noun, which was actually an attribute for the following noun (N+1) (translated to English e.g. "The sick writer had a cold (N) nose (N+1) …").The sentences in the control condition were built analogously, but word N was purposefully altered (keeping word length and frequency constant) to make its interpretation as a noun extremely unlikely (e.g. "The sick writer had a blue (N) nose (N+1) …"). In both conditions, the sentences were presented either following German standard orthography (Cap) or in lowercase spelling (NoCap). The capitalized nouns in the EXP/Cap condition should then prevent garden-path parsing, as capital letters can be recognized parafoveally. However, in the EXP/NoCap condition, we expected a garden-path effect on word N+1 affecting first-pass fixations and the number of regressions, as the reader realizes that word N is instead an adjective. As the control condition does not include a garden path, we expected to find (small) effects of the violation of the orthographic rule in the CON/NoCap condition, but no garden-path effect.As a global result, it can be stated that reading sentences in which nouns are not marked by a majuscule slows a native German reader down significantly, but from an absolute point of view, the effect is small. Compared with other manipulations (e.g. transpositions or substitutions), a lowercase letter still represents the correct allograph in the correct position without affecting phonology. Furthermore, most German readers do have experience with other alphabetic writing systems that lack consistent noun capitalization, and in (private) digital communication lowercase nouns are quite common.Although our garden-path sentences did: last words missing, see PDF!